Planning Commission's report of the Committee on India Vision 2020 and vision documents of some states. - India. Committee on India Vision 2020.; India. Committee on India Vision 2020.; Academic Foundation (New Delhi, India) (New Delhi : Academic Foundation, 2003)
Examines many important issues which include employment and education. This work covers issues related to population growth, food production, health, vulnerable sections of the population, transport, communication, energy self-sufficiency, water conservation and air quality, trade investment, peace, security and governance.
"The Planning Commission constituted a Committee on Vision 2020 for India in June 2000 under the chairmanship of Dr. S.P. Gupta, Member, Planning Commission"--Foreword.
oif 26/08/15
Loan
Keywords: Economic forecasting -- India; Social planning -- India; Political planning -- India; India -- Economic conditions; India -- Economic policy